2021
DOI: 10.1371/journal.pone.0243228
|View full text |Cite
|
Sign up to set email alerts
|

Availability and factors influencing community level handwashing facility in Ethiopia: Implication for prevention of infectious diseases

Abstract: Background Handwashing is one of the most effective ways to prevent transmission of infectious diseases. A substantial body of research has examined the status and determinants of handwashing facilities in healthcare settings and schools. However, its status at home in the community, especially in developing countries, remains unclear. This study aimed to examine the availability and factors influencing basic handwashing facilities at households in Ethiopia. Method We analysed the 2016 Ethiopian Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
(40 reference statements)
2
18
1
Order By: Relevance
“… 11 , 29 It was also only 8% households had handwashing facilities in Ethiopia which was very low. 10 On the other hand, multiple studies have shown that washing hands with soap or ash can reduce the risk of diarrheal diseases by 42% to 47% and this might save a million lives every year. Washing hands with soap and water also helps in the reduction of respiratory tract infections, and stunting among children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 , 29 It was also only 8% households had handwashing facilities in Ethiopia which was very low. 10 On the other hand, multiple studies have shown that washing hands with soap or ash can reduce the risk of diarrheal diseases by 42% to 47% and this might save a million lives every year. Washing hands with soap and water also helps in the reduction of respiratory tract infections, and stunting among children.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies in Ethiopia suggested that forgetting and a lack of any handwashing infrastructure hindered regular handwashing practice. 4 , 5 , 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odo and Mekonnen [ 18 ] established some of the factors that are associated with households that have handwashing facilities. These include; a better household wealth status, education status of the household head, having a radio and an improved latrine facility.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous studies, household infrastructure and wealth measured through a wealth index was an important factor in having water and soap at the handwashing station. 26,27 Taken together, our findings suggest that household infrastructure and water access challenges in this drought-prone setting should be considered when addressing hygienerelated behavior. 28 In particular, there should be an increased emphasis on addressing the needs of economically vulnerable groups through the development of, for example, pro-poor sanitation business models.…”
Section: Discussionmentioning
confidence: 69%